Pedagogia da pedagogia: o curso e sua identidade - Boccia, Margarete Bertolo (2016)
The identity of the Education School at present is the focus of our studies and reflections. Nuisance to the criticism received by the course, raised the hypothesis that there were ambiguities and contradictions, historical and legally built over the course of Pedagogy, which produced the different training requirements specified in the National Curriculum Guidelines for Education Course, bringing difficulty for the delimitation of their identity. The research study quantitative and qualitative featured a combination of procedures and techniques, in addition to historical rescue, literature and relevant legislation, a survey was carried out with students of the Faculty of Education of a private institution of higher education of S??o Paulo, in order to identify the views of students on their course, their training needs and issues considered important and controversial in the formation of a pedagogue. Held still, semi-structured in-depth interviews with the actors considered privileged discussions of course, choices and criticisms to the Faculty of Education in our country. Three interviews were conducted, the first with one of the rapporteurs of DCNP and two researchers from antagonistic positions on the issues surrounding the formation and the Faculty of Education. For guidance and organization of data four variables were constructed from the list of skills and competencies expected of graduates of the course, described in DCNP. The first variable considered was the time course load versus the formation of the pedagogue, represented by different training needs present in educational performance for children and other segments; the second variable brings the teacher's fields of activity in the teaching career versus the management career. The third variable brings the fields of activity in school spaces versus non-school spaces, be they educational spaces, non-formal education, informal or other distinct spaces. And the fourth variable, the theory versus practice. The theoretical frame of analysis used was Freirian with the choice of the categories autonomy, political content, educational practice and knowledge of teaching. The approximation of the results obtained in the opinion poll conducted with students and reports of respondents, the first variable on the workload of the course, students consider it satisfactory, as the rapporteur, but there is no agreement of the researchers who consider it insufficient. In the second variable, the students present agreement with one of the researchers, that there should be two courses of Pedagogy, one that would form the teacher and the other that would form the manager. This thought is different from the rapporteur and researcher 1 (so-called), that justify the possibility of co-existence of training for the teaching explanation to be understood in extended and not restricted sense. The third variable on performance in school and non-school spaces, students approached the rapporteur's thoughts and one of the researchers who understand that training is for performance in any educational space, as the researcher 2 indicates that this action should exist, but it is not possible to do it the way DCNP proposed and organize current courses. In the last variable there is no agreement between the rapporteur, researchers and students.